PENGARUH PENGERINGAN TERHADAP KANDUNGAN LEMAK CABE BESAR (CAPSICUM ANNUUM L.) - YULIASRI JAMAL; G. PANGGABEAN (Research Center for Biology-Indonesian Institute of Sciences, 1988)
YULIASRI JAMAL&G. PANGGABEAN. 1988 The effect of drying on the fat content of th chillies (Capsicum annuum L.). Berita Biologi 3(8) 374 - 376. The treating of chillies on various temperatures were studied in order to know their effect on the fat content.The chillies were dried in the refrigerator (12°C),in the room at ambient temperature (25°C ±2°C), in the sun shine (35°C ± 2°C) in the oven at various temperatures such as 40°C 50°C, 60°C, 70°C, 80°C, 90°C and 100°C.During the investigation were used cabe keriting and cabe besar biasa & it were obtained from the local market.The results of the observation that the highest fat content were found on the cabe keriting a 70 C drying as well as room temperature.The fat content of terated chillies, however, in the oven at 50°C, 60°C were similar 14%.Meanwhile,the dried chillies as the result on the sun shine was 3,5% fat content. The fat content of cabe besar biasa was significantly high at 70°C. The fat content of the chillies decreased rapidly on the treating in the sun shine.The chillies both cabe keriting and cabe besar biasa which were dried more than 60°C & in the sun shine, the pulp turned to brownish red, whereas the dried chillies in the refrigerator, at room temperature, 40°C, 50°C and 60°C the colour of the pulp were similar to the fresh fruits.